Unveiling The Effect of Testosterone Therapy on Sexual Dysfunction - Putu Gede Pradipta Mahardika Wijaya; I Gusti Agung Thede Surya Putra; I Putu Gede Sanjaya (International Journal Labs, 2024)
Male sexual dysfunction, including ED, PD, and PE, is prevalent, particularly in older men. Research has suggested that hormonal factors, specifically low total testosterone levels, may contribute to these conditions. TTh has been explored as a potential treatment for male sexual dysfunction, but studies have used varying assessment methods. This meta-analysis aimed to provide a comprehensive evaluation by using a consistent assessment tool, the International Index of Erectile Function (IIEF). Methods: Randomized controlled trials (RCTs) comparing TTh with placebo in adult men with sexual dysfunction were included. The primary outcome measure was the IIEF score. Studies were selected through a systematic literature search, and 16 RCTs met the inclusion criteria. Results: 16 studies were deemed from 98 studies was identified. The effect size testosterone therapy (Tth) in overall sexual dysfuction with standardized mean difference (SMD) 1.8, 95% CI 0.31 to 3.43. Impact of testosterone therapy on erectile dysfunction with Mean Difference (MD) 3.07, 95% CI 1.68 to 4.46. P-value 0.0001) (p<0.0001). Discussion: Testosterone plays a crucial role in regulating various aspects of male health, including sexual function. TTh has demonstrated positive effects on sexual function, particularly in improving erectile function. The time course of TTh effects suggests that improvements in libido and sexual activity can occur within weeks, while substantial improvements in erectile function may take several months. Additional assessment tools, such as the PDQ-Q4 and DISF-M-II, have also shown positive outcomes with TTh.